Diverticular disease of the small intestine - Suaya, Hadel (Cirugía del Uruguay, 2021)
The paper describes a case of diverticular disease of the small intestine complicated by difuse peritonitis due to perforation of one of the diverticula, includes a bibliographical review and up dates the subject with respect to its pathology, clinic and therapy. This disease is most frequently located in the high jejúnal sector at the level of the mesenteric border, and there is a high percentage ( 20 % ) with diverticula in the rest of the digestive tube. Anofoer characteristic is the lack of symptomatology other than inflamatory complications, obstruction, hemorrhage or perforation.